The use of data management planning among researchers in higher learning institutions: The case of the Nelson Mandela African Institution of Science and Technology in Tanzania - Neema Florence Mosha; Patrick Ngulube (Journal of eScience Librarianship, 2024)
This study assessed the use of data management plans among researchers at a selected higher learning institution (HLI) in Tanzania. A pretested structured questionnaire was administered to registered postgraduate students. Many of the respondents reported that a data management plan (DMP) was required before writing a research project and when a research project was submitted. The results also demonstrated that many respondents did not use any online DMP template tools to formulate their DMP although most of them were aware of available DMP template tools such as OpenDMP. Many respondents stated that the requirement of using a DMP were selection of a DMP format, updating the DMP regularly, having a short and to-the-point DMP and a well-structured DMP specifying the kinds and formats of the data to be acquired, generated, produced, and preserved. Meeting funders’ institutions, and publishers’ requirements, and ensuring that data are accurate, complete, and reliable were among the DMP benefits in HLIs identified by the respondents. Several challenges were revealed including a lack of awareness, competence, and guidelines to assist researchers using a DMP for their research projects. The conclusion is that researchers need to develop and use DMP template tools to plan, organize, and work on their research projects in addition to ensuring that they meet funders' requirements. It is recommended that HLIs should provide extensive training programs for raising awareness about DMPs among the researchers and to make DMPs a mandatory requirement for finalizing research projects among researchers, and not only for funding purposes.